Development of a PCR method to detect polymorphism of ace in optimisation of HMG-CoA reductase inhibitor / Nur Amalina Nasis - Nasis, Nur Amalina (2009)
Angiotensin-converting enzyme (ACE) is a major component in the renin-angiotension aldosterone system (RAAS) and has been studied as a candidate for development of some disease. Polymorphism of angiotensin-converting enzyme (ACE) means that there is variation in the nucleotide sequence of the ACE's gene due to insertion (I) or deletion (D). The aim of this study is to develop and validate a PCR based genetic test for identification of genetic variants of ACE. The primers were designed according to the gene and followed by reconstitution of primer working stock. The blood samples were already set up at the lab for this study but the samples collection of buccal and hair must be done. The samples were important as a template even different template have different amount of DNA. The Polymerase Chain Reaction (PCR) using the primers and different samples was done to amplify the sequence of ACE. The PCR component such as annealing temperature, magnesium concentration and primer concentration has been changed in order to get the desired product that amplified the ACE gene. The PCR method has been optimized to get the clear band in order to detect and identify the insertion (I) and deletion (D) of ACE gene. Based on the result of this study, it can be concluded that I/D polymorphism of ACE gene was successfully amplified by using the PCR. However, for further confirmation, the product that was obtained in this study would be sent for sequencing to compare it with the published sequences. The finding of this study can be used as a marker for optimization usage of drugs for example HMG-CoA reductase inhibitor (statins) for different individuals.